Study of the Effectiveness of Brain Exercise Training and Intensive Short-Term Dynamic Psychotherapy (ISDTP) on Emotional Self-Awareness of Mothers with Mentally Retarded Children in Ahvaz - Ghanavati, Maryam (2020)
Nowadays, study of the conditions of families with mentally retarded children, especially their mothers, is of great interest to researchers. Therefore, the present study aimed to investigate the Effectiveness of Brain Exercise Training and Intensive Short-Term Dynamic Psychotherapy (ISDTP) on Emotional Self-Awareness of Mothers with Children with Mentally Retarded Children in Ahvaz in the spring 2020. The statistical population of the study included all mothers of mentally retarded children in Ahvaz who were selected by available sampling method of 45 mothers and were divided into three groups of 15 (two experimental groups and one control group) by lot. The research design was experimental with pre-test and post-test with control group. The instruments used were Grant et al. (2002) Emotional Self-Awareness Questionnaire, which were completed in two stages before the intervention and at the end of the intervention. The results of the study using multivariate analysis of covariance and Bephroni post hoc test showed that the groups of brain exercise training and short-term dynamic psychotherapy in comparison with the control group are effective in increasing the emotional self-awareness of mothers of mentally retarded children. The results also showed that both methods are effective in increasing emotional self-awareness.